“If Pain Could Speak, What Would It Say?” Re-lational Inter/Intra-rogation of sickle cell disease: A Poetic (Inquiry) Insight. - Anumah, Peace (Murmurations: Journal of Transformative Systemic Practice, 2023)
If pain could speak, what would it say? If it could have a form, what would it look like? I start with these questions to illustrate the line of inquiry I am reframing as insight. The insights come from a conversation with a therapist warrior battling sickle cell disease (SCD). I use the language of therapist warrior for multiple reasons. To protect the anonymity of my conversational partner; to obscure her name but not her identity or infinite resourcefulness; to work with an archetype in a way that is congruent with the model of engagement I use within our conversations - Internal Family Systems (IFS), (Schwartz, 2013). I work with this model in my therapy practice. I draw on it in this paper to highlight the transformational power of externalising the pain experienced by the therapist I am conversing with. I will offer an overview of the model and an overview of the new language I am introducing in relation to methodology. IFS offers a different lens through which to view pain. Pain can be externalised as a “part”, no longer within the individual. This helps to empower the individual and their experience of pain. In this paper, I seek to highlight the resilience of the therapist I am conversing with and raise awareness of sickle cell disease. The paper actively examines the oppression and racialisation experienced by individuals with SCD from within the health care system. Care is contested. I use “re-lational inter-rogation/intra-rogation”, a methodology I am developing, to examine this. This way of engaging with conversational material highlights the importance of intentionally exploring relational changes after every re-connection or newfound acceptance between and within a group and connecting those insights with wider political forces. I use my embodied reflexivity for witnessing the impact, experiences, and happenings that occur during and after our dialogue. I illuminate my conversational partner’s resilience within the wider discourse of racialisation and marginalisation. Poems are transcribed from the conversation to add to the quality and aesthetics of the paper for the readers, as well as a reflexive process for me during and after my conversation with the therapist warrior. Poetry has a long history as a counter-narrative to the status quo and can be viewed as a decolonial, political act (van Rooyen and d’Abdon, 2020).